Princess Urduja From Tawalisi: Arabic Mirabilia And Philippine History - Donoso, Isaac (Tashwirul Afkar, 2025)
This article examines the figure of Princess Urduja of Tawalisi as narrated in Ibn Baṭṭūṭa’s Riḥla, and explores how this account was later incorporated into the historiography and national imagination of the Philippines. Tawalisi, a mysterious land mentioned only by Ibn Baṭṭūṭa, has long generated scholarly speculation, with proposed locations ranging from Sulu, Brunei, and Sulawesi to Pangasinan. José Rizal’s identification of Tawalisi with Pangasinan had a significant impact on Philippine historical consciousness, as it suggested the existence of a prosperous pre-Hispanic polity ruled by a warrior princess before the arrival of the Spaniards. This article, however, argues that the historical basis of Urduja’s story remains highly uncertain. Rather than treating the narrative as a reliable historical record, it is more appropriately understood within the framework of Arabic ‘ajā’ib literature: a tradition of writing on marvels, travel, and distant lands that blends fact, memory, legend, and imagination. In this sense, Urduja is not simply a historical figure, but a cultural construction that has contributed to the formation of Philippine national identity. Although her historical existence cannot be verified, her enduring role as a symbol of courage, independence, and the pre-colonial past remains significant within the imaginative history of the Philippines.